Remote sensing and GIS technology in Andros Island's environmental characteristics. - Vaiopoulos, D.; Vassilopoulos, A.; Evelpidou, N. (VI International conference ‘Protection and Restoration of the Environment, 2002)
Andros is the 2nd biggest island in Cyclades. Its morphology is intense and derives from the lithological and tectonical characteristics of the island. In this paper we studied Andro’s island environmental characteristics using Remote Sensing and GIS techniques. A GIS database was developed including all the corresponding geographical, geological, geomorphological and environmental characteristics. Moreover, an environmental map was developed at a 1:50.000 scale that elaborates all the above data. Remote Sensing techniques were also used in combination to the traditional cartographical methods, in order to locate with maximum accuracy all these data and input them in the GIS.